(untitled) (Cadernos de Sociomuseologia, 2026)
This article critically examines museum management processes in the twenty-first century through a case study of the National Coach Museum (Museu Nacional dos Coches, MNC) between August 2021 and January 2025. Drawing on the museum definition adopted by ICOM in 2022, which emphasises community participation, inclusion and sustainability, the study proposes a model of participatory and inclusive museum management centred on people, communities and the shared construction of knowledge. The research combines contributions from sociomuseology, participatory management theories and contemporary approaches that view museums as agents of social transformation. Methodologically, it employs Action Research and the Case Study method to analyse co-management, co-production and co-creation practices developed at the National Coach Museum. The study focuses on initiatives such as the Inclusive and Solidarity Museum project and the participatory exhibitions The Queen’s Tournament: The Solidarity of the Portuguese People, The National Coach Museum Through the Eyes of its Visitors, Long is the Journey, and A Cadeirinha: A Private and Urban Means of Transport. The findings demonstrate that structured community participation strengthens a sense of belonging, broadens audience diversity and reinforces the museum’s social role. At the same time, significant challenges remain, including institutional resistance to change, limited resources and the need to critically address the decolonisation of narratives and the use of Artificial Intelligence. The study concludes that adopting participatory models requires a paradigm shift in museum management, enabling national museums to become more inclusive, democratic and co-creative institutions. Social participation therefore emerges as a key factor in ensuring the sustainability and contemporary relevance of museums. Keywords: participatory museum management; co-management; co-creation; social museology; inclusion; National Coach Museum